Joint Power and Channel Allocation to Minimize Age of Information in Wireless Networks with Time-Varying Channels and Power Constraints - Chen, Guozhi; Chen, Yuchao; Wang, Jintao; Song, Jian (IEEE Vehicular Technology Conference, 2024)
In this paper, we consider the scenario where the base station (BS) transmits time-sensitive information to various users via shared orthogonal sub-channels. The BS allocates sub-channels and power to different users to complete the data transmission task in each time slot. The metric Age of Information (AoI) is adopted to measure the timeliness of information. We jointly optimize the transmitting decisions, the sub-channel assignments, and the power allocation schemes to minimize the average AoI of the users subject to the average and peak power constraints. We propose a dynamic scheduling policy based on the Lyapunov optimization method and then prove that the proposed policy can satisfy the power constraints and achieve a near-optimal AoI performance. Numerical simulations indicate that the proposed policy is stable and satisfies the power constraints, which validates the theoretical analysis.